The Global Seed Market, Competition Law and Intellectual Property Rights : Untying the Gordian Knot /: Untying the Gordian Knot. (February 2016) - Lianos, Ioannis; Katalevsky, Dmitry; (Director at the Skolkovo Foundation), Ivanov, Alexey
No abstract available